New structural alerts for Ames mutagenicity discovered using emerging pattern mining techniques. Issue 1 (5th November 2014) - Coquin, Laurence; Canipa, Steven J.; Drewe, William C.; Fisk, Lilia; Gillet, Valerie J.; Patel, Mukesh; Plante, Jeffrey; Sherhod, Richard J.; Vessey, Jonathan D.
Graphical Abstract: Abstract: Emerging pattern mining techniques have been applied to datasets of Ames mutagens. The discovered patterns give rise to clusters of compounds from large and biased datasets which are used to develop new structural alerts for mutagenicity in the Derek Nexus expert system.